Painting the Kitchen Tables: Exploring women’s domestic creative spaces through publication design - Brown, Ruby; Mortensen Steagall, Marcos (DAT Journal, 2023)
The spaces women take up in society have been shrouded in shame, disenfranchisement, and contention, with the kitchen as a focal point of this argument. This article aims to suggest ways in which women can take up space in the kitchen, this integral pillar of society that upholds connection and creativity as an art form. Adjacent to this subversive shift of connotation is the shifts within feminism, as feminist perspectives on women within kitchens develop alongside the historical movement. In this project, the researcher has utilised a post-positivist paradigm under an auto-ethnographic methodology to document, analyse, and celebrate the variations within feminist perspectives on creativity within domestic spaces through textile and publication design. In order to shift perspectives on these domestic spaces, the design outcomes paid tribute to feminist artists who made the kitchen their studio and others who captured the kitchen as an artistic contribution to the feminist perspectives on these spaces. Through heuristic methods of testing, experimentation, and physical outputs, the researcher curated a series of design artefacts that distil the visceral experiences of how women take up space in kitchens. Through publication design, there is a documentation of the shifting feminist perspectives on women’s domestic spaces through contrast and analysis of articles, poems, recipes, and artist insights. These contexts are supported by the tactility of the physical design outcome made using textile, pottery, and printed matter. The research distils and provides a destination for the celebration of ways in which women take up space within the kitchen and the integral artistic creations within those spaces.